Developments in Miniaturization of Gas Chromatography - Wardencki, Waldemar; Witkiewicz, Z. (Current Advances in Chemistry and Biochemistry Vol. 4, 2021)
The tendency towards miniaturization is visible in many areas of the wider word. The downsizing of many everyday used items (e.g. wristwatches, i-phones) is possible mainly due to the avaailability of newly developed technology. The same trend is also observed in many fields of analytical chemistry. It is related with the contemporary movement in analytics to perform analysis at the place where analytes are present. The miniaturization of conventional analytical instruments can provide many attractive features, e. g. reduced space requirements, better flexibility and faster results, without sacrifice in performance, and perhaps, with improved performance. The chapter provides a general overview of the progress and current status of miniaturization of one of the most widely used analytical technique – gas chromatography (GC). First, the general characteristics of miniaturized gas chromatographs and a brief history of the miniaturized GC systems is presented. Next, the technologies used for fabrication of miniaturized gas chromatographs and the developments of a key components of micro gas chromatographs (?GC) systems, i.e. injectors/preconcentrators, columns and detectors, based on microelectromechanical technology (MEMS), are discussed. In the last section, the hybrid miniaturized systems, with emphasis on coupling of gas chromatographs with mass and ion mobility spectrometers (MS and IMS), are discussed. Finally, the examples of selected applications of gas chromatographs with MS (GC-MS) and IMS (GC-IMS) are given.